Pelatihan Penggunaan Sistem Informasi Manajemen Rumah Sakit (SIMRS) Kepada Mahasiswa Praktek Kerja Lapangan Jurusan Administrasi Rumah sakit di RS. Siti Rahmah - Ronaldo Syahputra; Irohito Nozomi; Ahmad Junaidi (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
Technological advances have given birth to various kinds of innovations, one of which is the Hospital Management Information System (SIMRS). SIMRS is a tool in the process of making medical recaps for patients in hospitals. This is due to the daily activities of PKL (Field Work Practice) students who have to make reports about patient medical recaps.